Спряжений теплообмін плоских полімерних плівок, охолоджуваних на барабані - Горобець, В. Г. (Енергетика і автоматика, 2017)
Conjugate heat transfer of plane polymer films cooled drum V. Gorobets Polymer films are widely used in technology in the production of agricultural products, such as in greenhouses for growing vegetables, seedlings, flowers, etc., storage and packing of vegetables and a number of other technologies. In the production of polymer films used two main technological device - installation for forming blown film by cooling jet of cold air currents and installations for the production of flat film cooling them on a cylindrical drum. The basic principle of the devices in the formation of flat polymer films with cooling drum is intense heat transfer from the selection of film, which is extracted from the extruder by contact with a drum that cools the internal coolant. In the initial field of cooling polymer film on the drum for pressing the film to the surface using roller or clamp or clip made jet of air that comes out of the slot channel. It is important to create optimal conditions for the selection of heat transfer from the polymer film when it chilled at the stage of the melt and crystallization, which makes it possible to save resources in the development of plants for the production of flat polymer films. The purpose of research - to analyze the thermal processes occurring when forming a flat polymer film cooling on the drum, to develop mathematical models of transport processes, perform numerical calculation of parameters of heat transfer and make recommendations for improving the design of equipment for the production of flat polymer films. As a result of the research the following results are obtained: 1) there are developed a mathematical model of the processes of heat transfer when forming a flat polymer film on cooling drum; 2) numerical calculation are conducted and the influence of the main dynamic, thermal and geometric parameters on the cooling polymer film are found; 3) comparison of the results of numerical calculations with experimental data are conducted and their satisfactory coincidence are obtained/